Facile in situ synthesis of a carbon quantum dot/graphene heterostructure as an efficient metal-free electrocatalyst for overall water splitting. Issue 11 (18th January 2019) - Zhao, Man; Zhang, Jingjuan; Xiao, He; Hu, Tianjun; Jia, Jianfeng; Wu, Haishun
Abstract : A CQD/graphene hybrid used as an efficient metal-free electrocatalyst for water splitting was in situ synthesized by a facile two-step procedure. Abstract : A metal-free carbon quantum dot (CQD)/graphene hybrid was in situ synthesized through a simple novel two-step procedure. The hybrid showed superior HER and OER activity attributed to synergistic effects between the defect-rich CQDs and conducting graphene support.